2022
DOI: 10.1186/s12879-022-07912-3
|View full text |Cite|
|
Sign up to set email alerts
|

COVID-19 impact on index testing services and programmatic cost in 5 high HIV prevalence Indian districts

Abstract: Background Restrictions to curb the first wave of COVID-19 in India resulted in a decline in facility-based HIV testing rates, likely contributing to increased HIV transmission and disease progression. The programmatic and economic impact of COVID-19 on index testing, a standardized contact tracing strategy, remains unknown. Methods Retrospective programmatic and costing data were analyzed under a US government-supported program to assess the pand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The probable reason for this could be linked to increased awareness for better seeking of appropriate protective health services among youths as compared to adults who tend to assume matters related to their health. These study findings were in agreement with two other studies conducted in India and Kenya [10,11], However, another study done in Tanzania was contrary to these findings [12].…”
Section: Discussionsupporting
confidence: 91%
“…The probable reason for this could be linked to increased awareness for better seeking of appropriate protective health services among youths as compared to adults who tend to assume matters related to their health. These study findings were in agreement with two other studies conducted in India and Kenya [10,11], However, another study done in Tanzania was contrary to these findings [12].…”
Section: Discussionsupporting
confidence: 91%
“…This also contributes to achievement of 95-95-95 targets by UNAIDS. 29,30 There was no delay in the initiation of the treatment. All the patients reported the healthcare professionals as their source of information regarding treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported a production error. The incorrect version of Figure 4 was published, which omits the value “858” in the first blue bar.…”
mentioning
confidence: 99%